CARDIOVASCULAR SYSTEM ASSESSMENT IN WORKERS OF MINING INDUSTRY - Furkat Y. Imanov; Mukaddaskhon A. Khamrakulova (Central Asian Journal of Medicine, 2025)
We conducted a medical examination of 649 male workers employed at the underground sites of the Razvedochnaya, Kairagach, Semguron, and Samarchuk mines within the Angren Ore Management Group, as well as 80 administrative staff members to assess the impact of occupational environmental factors on their health. Among those examined, 42% were found to have cardiovascular pathologies. These included hypertension in 30% of the subjects and ischemic heart disease in 12%. An evaluation of the cardiovascular condition of both the primary and control groups revealed several changes in the functional status of various systems and an unfavorable trend in indicators associated with increased work experience. For workers with 5-10 or more years of service, this indicator was 2.5 times higher compared to surface workers, and the prevalence of individuals with vegetovascular dystonia was 7.2 times greater. Cardiovascular pathologies were twice as common among tunneling workers, underground machine operators, support installers, and drill operators.